2000 years of forest dynamics in the Ecopark Raslången, South Sweden - Östh, Sara (2009)
Knowledge of the local long-term vegetation history is an essential basis for restoration plans and ecological management. This study was conducted in the future Ecopark Raslången, situated outside Olofström in Southern Sweden. The aim was to 1) assess the forest history of the Ecopark Raslången during the last 2 000 years, 2) investigate the changes in forest composition that have taken place during the last century, 3) discuss the local vegetation changes in relation to biodiversity and 4) incorporate this knowledge into the practical forest management. A pollen analysis was conducted from a peat core taken from a small mire in the Ecopark. The results show that the total share of forested land has decreased during the last 2 000 years. Broadleaved species such as Quercus and Tilia have decreased, while Pinus, Picea and Fagus have increased. The most drastic changes in the forest composition have taken place during the last 200 years. Human impact has been a part of the forest dynamics for a long period, but the nature of human impact has changed over time. During AD 850- 1850 the forest was used extensively for grazing, with clearings to create fields for agriculture. Today human impact is most clearly seen in the stand structure and species composition, most notably in even-aged monoculture stands of Picea. Restoration and management of the future Ecopark should consider forest history, biodiversity and social values. In a local forest history perspective, today's large share of Fagus makes the share of broadleaved trees, all species combined, fairly constant over time. In a regional perspective, however, more broadleaved trees are needed. More broadleaved trees would benefit the biodiversity and social aspects of the Ecopark. The share of broadleaved trees therefore ought to be increased on the expense of even-aged monoculture Picea stands. Visitors to the Ecopark should be informed about what is done in the Ecopark and why, to create a better understanding of the management aims.